1999
DOI: 10.1136/jnnp.66.4.541
|View full text |Cite
|
Sign up to set email alerts
|

Affective symptoms in multiple system atrophy and Parkinson's disease: response to levodopa therapy

Abstract: The objective was to determine the extent to which psychiatric disturbances (especially mood disorders) generally considered poor prognostic factors, are present in patients with striatonigral (SND) type multiple system atrophy (MSA) compared with patients with idiopathic Parkinson's disease (IPD). The Hamilton depression scale (HAM-D), brief psychiatric rating scale (BPRS), and Unified Parkinson's disease rating scale (UPDRS) were administered to clinically probable non-demented patients with SND-type MSA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 27 publications
5
45
0
Order By: Relevance
“…Fourth, a larger cohort of patients followed-up for extended time periods will be required to substantiate the nonlinear progression of parkinsonism observed in our study. Fifth, although the UPDRS has been the instrument of choice to measure motor disability in MSA so far [1,3,17,21], it does not accurately reflect the complex motor picture of MSA owing to the mixed cerebellar and parkinsonian motor impairment that occurs in most MSA patients [16]. However, the UPDRS-III has been shown to provide a useful severity measure of parkinsonism in MSA [21].…”
Section: Discussionmentioning
confidence: 96%
“…Fourth, a larger cohort of patients followed-up for extended time periods will be required to substantiate the nonlinear progression of parkinsonism observed in our study. Fifth, although the UPDRS has been the instrument of choice to measure motor disability in MSA so far [1,3,17,21], it does not accurately reflect the complex motor picture of MSA owing to the mixed cerebellar and parkinsonian motor impairment that occurs in most MSA patients [16]. However, the UPDRS-III has been shown to provide a useful severity measure of parkinsonism in MSA [21].…”
Section: Discussionmentioning
confidence: 96%
“…Dopaminergic antiparkinsonian drug therapy may therefore have antidepressant effects. Studies of PD patients with advanced disease and motor fluctuations with [30] and without [31] baseline depression have shown improvement of depression and mood after receiving levodopa. In another study, only minor beneficial effects of levodopa on mood in nondepressed, mildly affected, and drug-naive patients were reported [32‱].…”
Section: Effects Of Antiparkinsonian Drugs On Neuropsychiatric Symptomsmentioning
confidence: 98%
“…MSA-P patients showed significant deficits in the tests previously shown to be sensitive to frontal lobe dysfunction [83, 85, 86, 88]. There are several studies demonstrating that MSA-P patients have apraxias [91,92,93] or depressive state [94,95,96]. In comparisons among PD and MSA-P and progressive supranuclear palsy, although results were not consistent, all studies showed patients with progressive supranuclear palsy were most severely impaired in cognitive function.…”
Section: Multiple System Atrophymentioning
confidence: 99%